Definition and Research Areas in the Geographical Study of Hotel Services - Kowalczyk, Andrzej (Turyzm/Tourism, 2001)
Academics representing many different fields, including geography, have becom e interested in hotel services as a result of their recent dynamic development. Hotels are the object of analysis in both the geography of tourism, the geography of services and urban geography. The complex character of the phenomenon raises the question of whether the geography of hotel services should becom e an independent study area.